Finite Element Analysis of the thermo-Mechanical Behavior of composite Pipe Elbows under Bending and Pressure loading (Fracture and Structural Integrity, 2019)
Elbows under load experience more stress and strain than straight tubes. The strength of the composite tubes plays an important role in their use, the damage under a thermomechanical behavior of a composite tubular structure bent between two linear parts is studied in this work. The HASCHIN criterion model is used through finite element analysis. The main objective is to predict the effect of the main parameters by curves of torque, using the calculation code ABAQUS. These evaluative parameters are addressed to the geometrical conditions of the elbow, in loading mode on the pressurized structures and to the danger of the defect, hence the advantage of using Shell elements as a structure. The numerical results obtained illustrate that the parameters studied condition the level and the mode of failure as well as the response of composite elbows.
Keywords: FEM; Damage; Elbows; Hashin criterion; Shell element